Colorimetric determination of phenytoin using indoxyl sulfate capped silver nanoparticles. Issue 26 (17th June 2019) - Khoubnasabjafari, Maryam; Salari, Rana; Samadi, Azam; Jouyban-Gharamaleki, Vahid; Jouyban, Abolghasem
Abstract : A simple and sensitive colorimetric probe based on aggregation of indoxyl sulfate capped silver nanoparticles was proposed for the detection of trace amounts of phenytoin. Abstract : A simple and sensitive colorimetric probe based on aggregation of indoxyl sulfate capped silver nanoparticles (InS-AgNPs) was proposed for the detection of trace amounts of phenytoin (PHT). InS-AgNPs were synthesized via a simple procedure and applied for the quantification of PHT in exhaled breath condensate samples. It was found that in the presence of PHT, the intensity of the InS-AgNP absorption peak at 396 nm is decreased and a new peak around 530 nm appeared gradually accompanied by a color change from yellow to pink. The characterization of InS-AgNPs and the mechanism of the colorimetric assay under optimum conditions were obtained by UV-vis spectroscopy, transmission electron microcopy (TEM), energy dispersive X-ray spectroscopy analysis and fluorescence spectroscopy. Under the optimum conditions, the calibration graph of the assay was linear in the range of 25–450 μg L −1, with a detection limit of 10 μg L −1 . The developed method was successfully applied for the analysis of spiked EBC samples with PHT.